2009
DOI: 10.1111/j.1600-0706.2009.17698.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal limitation inferred from an experimental translocation ofLomatium(Apiaceae) species outside their geographic ranges

Abstract: Determining limitations on poleward range expansion is important for predicting how climate change will alter the distribution of species. For most species, it is not known what factors set their distributional limits and the role dispersal limitation might play if range-limiting factors were altered. We conducted a transplant study of three related and cooccurring Lomatium species at their northern range limits to test competing hypotheses of range limitation. We added seeds to experimental plots inside and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 61 publications
(60 reference statements)
3
27
0
Order By: Relevance
“…Because the species is long-lived, it may take years before the population can be judged as sustainable, but the preliminary indications are that the populations are doing well. In a comparative outside-of-range northward introduction trial of one rare species, Lomatium dissectum with two co-occurring common congeners, Marsico and Hellmann (2009) found that the species survived well or better outside of range than within range, at least when the vegetative community remained intact. Examples of south Florida endangered species translocations in novel habitat with at least first generation recruits are Jacquemontia reclinata House (Maschinski & Wright 2006) and Lantana canescens (Possley, Maschinski, Rodriguez, & Dozier 2008).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because the species is long-lived, it may take years before the population can be judged as sustainable, but the preliminary indications are that the populations are doing well. In a comparative outside-of-range northward introduction trial of one rare species, Lomatium dissectum with two co-occurring common congeners, Marsico and Hellmann (2009) found that the species survived well or better outside of range than within range, at least when the vegetative community remained intact. Examples of south Florida endangered species translocations in novel habitat with at least first generation recruits are Jacquemontia reclinata House (Maschinski & Wright 2006) and Lantana canescens (Possley, Maschinski, Rodriguez, & Dozier 2008).…”
Section: Discussionmentioning
confidence: 97%
“…As this study demonstrates, microhabitats that were not historically known may prove to be optimal for species' survival and growth. Dispersal limitation has been demonstrated to limit species ranges (e.g., Marsico & Hellmann 2009) and can occur at fine scales of a few metres (Primack & Miao 1992;Eriksson 1998). Because the pine rockland/transverse glade ecosystem of A. herbacea var.…”
Section: Discussionmentioning
confidence: 99%
“…A latitudinal decline in genetic diversity, especially in terms of allelic richness, has been commonly found in high-latitude Northern Hemisphere tree lineages (e.g. Comps et al, 2001;Marsico and Hellmann, 2009;Ohsawa and Ide, 2011). Yet there are exceptions to this general pattern.…”
Section: Introductionmentioning
confidence: 98%
“…Small gaps created by raking provide more light, nutrients and lower competition from the surrounding vegetation (Morgan 1997), whereas individuals are more exposed to harsh conditions (more desiccation, herbivory; Foster 2001, Kolb et al 2007, Kotorová and Lepš 1999, Morgan 1997. Germination and initial establishment are, therefore, positively affected, while survival is reduced by disturbance (Foster and Gross 1997, Foster et al 2004, Jakobsson and Eriksson 2000, Janeček and Lepš 2005, Křenová and Lepš 1996, Marsico and Hellmann 2009. At the end of the experiment, ca, 1.5 times more surviving individuals were still found in disturbed plots; of those, 16 individuals reached reproductive stage in undisturbed plots against 17 in disturbed ones.…”
Section: Discussionmentioning
confidence: 97%